Randomised controlled trial of a general practice programme of home based exercise to prevent falls in elderly women. Issue 7115 (25th October 1997) - Campbell, A John; Robertson, M Clare; Gardner, Melinda M; Norton, Robyn N; Tilyard, Murray W; Buchner, David M
Abstract: Objective: To assess the effectiveness of a home exercise programme of strength and balance retraining exercises in reducing falls and injuries in elderly women. Design: Randomised controlled trial of an individually tailored programme of physical therapy in the home (exercise group, n=116) compared with the usual care and an equal number of social visits (control group, n=117). Setting: 17 general practices in Dunedin, New Zealand. Subjects: Women aged 80 years and older living in the community and registered with a general practice in Dunedin. Main outcome measures: Number of falls and injuries related to falls and time between falls during one year of follow up; changes in muscle strength and balance measures after six months. Results: After one year there were 152 falls in the control group and 88 falls in the exercise group. The mean (SD) rate of falls was lower in the exercise than the control group (0.87 (1.29) v 1.34 (1.93) falls per year respectively; difference 0.47; 95% confidence interval 0.04 to 0.90). The relative hazard for the first four falls in the exercise group compared with the control group was 0.68 (0.52 to 0.90). The relative hazard for a first fall with injury in the exercise group compared with the control group was 0.61 (0.39 to 0.97). After six months, balance had improved in the exercise group (difference between groups in change in balance score 0.43 (0.21 to 0.65). Conclusions: An individual programme of strength and balance retraining exercises improved physical function and was effective in reducing falls and injuries in women 80 years and older.